Boosting conceptual thinking in a programming course – An ontology-based approach - Barros, João Paulo (2023)
Students constantly have to learn and relate new concepts. However, those multiple relations are easily not given enough attention as their practical application is often given priority. Hence students are left with incomplete reflection on the subject matter, which quickly implies a surface learning of many essential contents and relations. Here, we propose using simple textual languages for students to express relations between concepts. Students’ feedback was highly positive, and they recognized the usefulness of the activity to better reflect and understand multiple intertwining concepts in an object-oriented programming course.